Optimization of microstructure and properties of composite coatings by laser cladding on titanium alloy. Issue 2 (15th January 2021) - Liu, Ya'nan; Yang, Lijun; Yang, Xuejiao; Zhang, Tiangang; Sun, Ronglu
Abstract: Recently, the current technological progress in developing laser cladding technology has brought new approaches in surface modification of titanium alloys. Herein, composite coatings were fabricated by the laser cladding process on Ti811 alloys using a coaxial powder feeding method. A comprehensive study was performed on the laser energy density (Led ) and CeO2 content on the structure distribution, microhardness and tribological properties of the coatings. In addition, the growth mechanism of the TiC–TiB2 structure was studied based on the Bramfitt two-dimensional lattice mismatch theory. The results indicated that the phase composition of the coating mainly contained TiC, TiB2, Ti2 Ni, and α-Ti. The optimized coating contributed to uniform microstructure distribution and fine grain size when Led was 45 J/mm 2 and the CeO2 content was 2 wt%, playing an important role in the best forming quality and properties. Besides, the high matching degree of an interface between TiC (111) and TiB2 (0001) contributed to the TiC–TiB2 composite structure, which positively influenced the grain size and distribution of TiC. The microhardness and wear resistance of the 2Ce coating was dramatically enhanced due to the fine grain strengthening and dispersion strengthening effects of CeO2, contributing directly to generate a high average hardness of 811.67 HV0.5 with a lower friction coefficient.